Schisandrin B Attenuates Airway Inflammation by Regulating the NF-κB/Nrf2 Signaling Pathway in Mouse Models of Asthma - Yaqin Chen; Yu Kong; Qili Wang; Jian Chen; Hua Chen; Huihui Xie; Lan Li (Journal of Immunology Research)
Background. Asthma is a complex inflammatory disorder that plagues a large number of people. Schisandrin B is an active ingredient of the traditional Chinese herbal medicine Schisandra with various proven physiological activities such as anti-inflammatory and antioxidant activities. In this study, we explored the anti-inflammatory and antioxidant effects and provided the mechanistic insights into the activity of schisandrin B in a mouse model of ovalbumin- (OVA-) induced allergic asthma. Methods. Male BALB/c mice were sensitized and challenged with OVA to induce asthma and treated with various doses (15 mg/kg, 30 mg/kg, and 60 mg/kg) of SCH to alleviate the features of allergic asthma, airway hyperresponsiveness, inflammatory response, OVA-specific immunoglobulin (Ig)E level, and pathological injury. Results. Schisandrin B significantly attenuated the airway hyperresponsiveness induced by OVA. Moreover, schisandrin B administration suppressed inflammatory responses, reduced the level of IgE, and attenuated pathological injury. Mechanistically, schisandrin B treatment promoted the activation of nuclear erythroid 2-related factor 2 (Nrf2), but suppressed the stimulation of the NF-κB pathway caused by OVA. Conclusion. Taken together, our study suggests that schisandrin B attenuates the features of asthmatic lungs by inhibiting the NF-κB pathway and activating the Nrf2 signaling pathway.